(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Lateral internal sphincterotomy (LIS) remains the gold standard surgical treatment for chronic and acute anal fissures refractory to conservative management. However, the optimal technique—cutting versus coagulation of the internal anal sphincter—continues to be debated, particularly concerning postoperative complications such as anal incontinence and bleeding. Objective: This study aimed to compare the postoperative outcomes between the cutting and coagulation methods of internal anal sphincter division in patients undergoing LIS for acute anal fissure. Methods: A prospective comparative analysis was conducted at a tertiary care setting from 1st June 2025 till 30th November 2025 (over a period of 6 months) on 90 patients (divided into groups of 2 each having equal number of patients) presenting with acute anal fissure who underwent lateral internal sphincterotomy using either the cutting technique (sharp dissection with scalpel) or the coagulation technique (electrocautery). Postoperative outcomes, including anal incontinence and postoperative bleeding, were recorded and analyzed. Statistical evaluation was performed using Fisher’s exact test/chi square test, with a p-value < 0.05 considered significant. Results: A total of 90 patients were included in the study, comprising 44 in the cutting sphincterotomy group and 46 in the coagulation group. Postoperative anal incontinence was reported in 3 (6.8%) patients in the cutting group and 6 (13.0%) in the coagulation group. The difference was not statistically significant (Fisher’s exact test, OR = 0.49, p = 0.486). Postoperative bleeding was observed in 6 (13.6%) of cutting sphincterotomies compared to 2 (4.3%) of coagulation sphincterotomies. Although bleeding was numerically more frequent in the cutting group, this difference did not reach statistical significance (Fisher’s exact test, OR = 3.47, p = 0.153). Conclusion: Both cutting and coagulation methods of internal anal sphincter division provide effective surgical management for acute anal fissure, with comparable postoperative outcomes. The choice of technique may thus be based on surgeon preference, available equipment, and individual patient considerations rather than significant differences in complication rates.